Preferential growth of Au on CdSe quantum dots using langmuir-blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2014)
Oleyl amine capped CdSe quantum dots (QD) were synthesised by hot injection technique. These QDs formed a self-assembled monolayer on an aqueous subphase of a Langmuir-Blodgett (LB) trough. Here, in this report we introduced a simple but very efficient route to form a metal (Au)-QD hybrid nanostructure via the LB technique. In this method, the metal counterpart of the hybrid nanostructure could be deposited exclusively on one side of the QDs. The formation of stable monolayer of QDs was evidenced from a surface pressure-area (P-A) isotherm. The development of gold tip was confirmed and monitored by detailed TEM study on the monolayer deposited on TEM grids from the LB trough. Other characterizations like UV-Vis spectroscopy, FTIR, XPS and EDX also suggested the same. Oleyl amine was shown to act both as a reducing agent as well as a capping agent in this strategy.